2010
DOI: 10.1007/s00277-010-0957-6
|View full text |Cite
|
Sign up to set email alerts
|

Can decreasing smoking prevalence reduce leukemia mortality?

Abstract: Previous studies have demonstrated a modest association between smoking and leukemia particularly for myeloid disorders. Our objective was to examine whether changing trends in cigarette smoking prevalence nationally and within selected states parallel similar trends in mortality from leukemia. Trends in national smoking rates were correlated with trends in leukemia mortality rates obtained from the Centers for Disease Control and Prevention and the Surveillance Epidemiology and End Results registry, respectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…In a study published by our group earlier, 24 we had shown that leukemia mortality has decreased overall in the United States in parallel with decreased smoking. Analyzed on a state-specific basis, leukemia mortality has decreased in states where smoking rates declined markedly but remained unchanged where smoking prevalences were relatively stable suggesting that declining rates of leukemia mortality are associated with changing patterns of smoking behavior.…”
Section: Discussionmentioning
confidence: 88%
“…In a study published by our group earlier, 24 we had shown that leukemia mortality has decreased overall in the United States in parallel with decreased smoking. Analyzed on a state-specific basis, leukemia mortality has decreased in states where smoking rates declined markedly but remained unchanged where smoking prevalences were relatively stable suggesting that declining rates of leukemia mortality are associated with changing patterns of smoking behavior.…”
Section: Discussionmentioning
confidence: 88%
“…28 In addition, a national study in the United States found that leukemia deaths decreased in states where smoking rates decreased but remained unchanged in states where smoking prevalence remained relatively constant. 29 In a study in Europe, it was shown that the trend of mortality due to leukemia from the years 1970 to 2009 decreased in most European countries, and the age group of 0-14 witnessed the most significant decrease (AAPC = -3.7%) for men and (-3.8%) women. Also, in the age group of 15-44 years, AAPC was -2% for both sexes.…”
Section: Discussionmentioning
confidence: 99%
“… 28 In addition, a national study in the United States found that leukemia deaths decreased in states where smoking rates decreased but remained unchanged in states where smoking prevalence remained relatively constant. 29 …”
Section: Discussionmentioning
confidence: 99%
“…However, it is the seventh cause of YLL due to premature death in the world (Fitzmaurice et al, 2015). Increased incidence of leukemia is attributable to risk factors such as obesity and smoking (Varadarajan et al, 2010;Chu et al, 2011) both being common risk factors in Yazd (Namayandeh et al, 2011), although further analysis is required to identify other risk factors in the region.…”
Section: Discussionmentioning
confidence: 99%